Moves Towards an Islamic Common Market: Evaluation of the Potentials - Said Jafarli (Journal of Economic Cooperation and Development, 2017)
The Organization of Islamic Cooperation members had proposed the establishment of an Islamic Common Market among themselves in the early 1970s. This notion currently listed among the core objectives of the Organization and, to this end, the members adopted the TPS agreement in 1990. This study provides the first systematic and comprehensive evaluation of the TPS signatories' potential to increase economic cooperation by applying five different trade indexes. The findings reveal different characteristics of the TPS countries and shed light on their potential for enhancing economic cooperation. In general, the results are in favor of the establishment of a Preferential Trade Agreement among the TPS signatories.
Keywords: F10; F14; F13; F15; F40; F50; F53; 330; Islamic Common Market; Export potentials; Trade Intensity Index; Growth Orientation of Markets Index; Trade Complementary Index; Herfindahl-Hirschman Market Concentration index; Herfindahl-Hirschman Product Concentration index; Organization of Islamic Cooperation; Trade Preferential System among the Member States of the OIC; TPS-OIC